Tirgvedības procesa analīze Veselības ministrijas Katastrofu medicīnas centrā. - Krapauska, Inita (Latvijas Universitāte, 2007)
Bakalaura darbs izstrādāts par Veselības ministrijas Katastrofu medicīnas centra tirgvedības procesiem, funkcijām, uzdevumiem un mērķiem. Darba tēma “Tirgvedības procesa analīze Veselības ministrijas Katastrofu medicīnas centrā”. Bakalaura darbs ietver informāciju par Veselības ministrijas Katastrofu medicīnas centru un tā darbību, raksturojošos rādītājus, vadības darbību un salīdzinošos rādītājus par valsts ieguldījumu un atbalstu veselības aprūpes sistēmā, darbībā un attīstībā. Darbs ietver teorētisko un praktisko daļu, kurā uzskatāmi apkopoti raksturojošo rādītāju rezultāti. Katras nodaļas apakšnodaļu darba autore sāk ar teorētisko apskatu par konkrēto jautājumu, un tad izklāsta kā tas izpaužas konkrētā vidē – Katastrofu medicīnas centrā. Bakalaura darbā ir apskatīti jautājumi, atbilstoši darba mērķiem un uzdevumiem, kā arī tiek apstiprināta izvirzītā hipotēze, ka valstij pievēršot lielāku uzmanību Katastrofu medicīnas centra darbības nozīmīgumam, piešķirot papildus finansējumu, atbalstot jaunus projektus, attīstot tādus higiēnas faktorus kā darba vietas apstākļi, darba algas palielināšana un labāka informācijas aprite, vēl vairāk uzlabotu Katastrofu medicīnas centra darbinieku ikdienas smago darbu. Par pamatu bakalaura darbam tika izmantoti galvenie Katastrofu medicīnas centra darbību regulējošie dokumenti, dokumenti par personālu, informācija un salīdzinošie statistiskie dati par medicīnas iestādēm un valsts ieguldījumu medicīnas sistēmas attīstībā. Bakalaura darba nobeigumā ir izstrādāti un apkopoti secinājumi par Veselības ministrijas Katastrofu medicīnas centra darbību un tirgvedības procesiem. Darbs sastāv no 74 lapām, 7 tabulām, 20 attēliem, 2 pielikumiem, kā arī ir izmantoti Latviešu, angļu un krievu valodā izdotie literatūras avoti par tirgvedības izpēti, tās procesiem un norisi un LR Veselības ministrijas Katastrofu medicīnas centra iekšējās dokumentācijas un publikāciju materiāli.

Bachelor paper has been developed about the marketing processes, functions, tasks and goals of the Ministry of Health Centre of Emergency and Disaster medicine. Theme of the paper “Analysis of marketing processes in the Ministry of Health Centre of Emergency and Disaster medicine”. Bachelor paper includes information about the Ministry of Health Centre of Emergency and Disaster medicine and activities of the centre, characterizing indicators, management activities and comparative indexes about the contributions of the state and support to the health care system, actions and development. Paper includes theoretical and practical part summarizing results of the characterizing indicators. Author begins the subsection of each chapter with the theoretical review about the concrete issue and then discloses the issue in the real environment – Centre of Emergency and Disaster medicine. Main task of the Centre of Emergency and Disaster medicine is to coordinate and supervise emergency medical aid, coordinate supervision of the emergency situations with other public services included in the rescue system, as well as contact with the foreign medical resources in case of the lack of the local resources, as well as for the elimination of the consequences caused by the emergency situations. Centre of Emergency and Disaster medicine is the only institution in Latvia providing unified implementation of the emergency medical policy in Latvia. Bachelor paper examines issues respective to the goal and tasks of the paper, as well as sets a hypothesis that more attention provided by the state to the significance of the activities of the Centre of Emergency and Disaster medicine, by providing additional foundations, supporting new projects and developing factors of hygiene like improved work place conditions, increase of the salary and enhanced circulation of information that could improve the hard everyday work of the Centre of Emergency and Disaster medicine more yet General regulating documentation of the Centre of Emergency and Disaster medicine, documents about personnel, information and comparative statistic data about medical institutions and state investments in the development of the medical system were used as a basis of the Bachelor paper. In the conclusion of the Bachelor paper final provisions about the activities and marketing processes of the Centre of Emergency and Disaster medicine have been summarized. Paper consists of 74 pages, 7 tables, 20 figures, 2 attachments, publications of marketing analysis and marketing processes in Latvian, English and Russian, as well as regulations and documents of the Ministry of Health Centre of Emergency and Disaster medicine.
The analysis of marketing process at the Ministry of Health Centre of Emergency and Disaster medicine.
Keywords: Vadībzinātne